Factors influencing malnutrition among the children of under 5 years - Bajracharya, Shanti; Subedi, Anup (Journal of Chitwan Medical College, 2017)
Objectives: Childhood is the time of active growth in terms of physical size, mental, emotional and psychological development. Nutritional status is the proxy indicator for assessing the health status of the entire population and one of the major predictors of child survival. Despite the various efforts, malnutrition among children is remaining as one of the major public health problems in Nepal. Objective: The objective of this study was to assess the factors influencing malnutrition among the mother of the children aged 6 to 59 months. Method: A descriptive exploratory study using non-probability purposive sampling method was conducted with 79 paired of mother with children, residing in Itahari ward number 2. Data were collected by interview technique using semi-structured questionnaires and analysis was done by using SPSS version 20 using descriptive and inferential statistics. Results: The mean age of the child was 32 months and standard deviation was 17.05. The prevalence of underweight, wasting and stunting was found to be 16.4%, 11.3 % and 7.6% respectively. Likewise, 17.06 % of the children were found below < -2 S.D on the basis of BMI per age of the children. Furthermore, it was found that there was significant association between educational status of mother with the malnutrition (underweight) as p-value was <0.05. Conclusion: Malnutrition is the major health problem in under 5 children. The prevalence of malnutrition can be decreased by improving the caretaker’s educational level through different awareness programmes based on the factors responsible for that.